The Role of Language in Shaping Power Relations in Educational Settings - Calvyn Sepanya Siregar; Erick Saut Maruli Sihombing; Daniel Saputra Gurning; Partohap Saut Raja Sihombing (Young Journal of Social Sciences and Humanities, 2026)
In educational environments, language is essential not only as a teaching tool but also as a means of establishing, upholding, and occasionally contesting power dynamics. This article investigates how language use in educational settings affects participation, authority, control, and identity. The study employs a qualitative research design grounded in Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA) to uncover implicit power relations present in educational discourse. Data were gathered through non-participant observations and audio recordings of English classroom interactions at a public junior high school in Pematangsiantar, North Sumatra. The findings reveal that teacher talk significantly dominates classroom interaction, utilizing imperative forms, closed-ended questioning, and the Initiation–Response–Feedback (IRF) sequence to maintain institutional authority. This dominance positions the teacher as the primary authority while limiting students’ opportunities to initiate interaction or negotiate meaning. The study concludes that understanding linguistic power is vital for supporting more inclusive and equitable teaching methods that redistribute power more effectively.